The relationship between Understanding and Being In Heidegger philosophy (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This paper discusses the relationship between understanding and being at the one of most important existentialist philosophers, a German philosopher Heidegger. Based on the study of this relation ship and interpreted in his philosophy, In an attempt to identify a way to achieve their being Which is the existence of assets, and show the meaning ofdasein and being, In addition to interpret the meaning of human existence and its importance because he is the only one who can ask a question of existence. in an attempt to identify the elements of this existence and understanding of which represents one of them, in order to distinguish between authentic existence and pseudo-existence, and clarify an experience anxiety and it’s importance and the necessary mechanisms to get to authentic existence, through a series of analyzes of the notions of understanding and being in Heidegger philosophy, In an attempt to analyze the moments of existence which are: (World)– (exist in the world) –(presence in the world)